ANALISIS DAMPAK PROGRAM WIRAUSAHA MERDEKA TERHADAP PERTUMBUHAN USAHA ROBI TOAST DI UNTAG SURABAYA - Aqila Shafa Zatalini; Pregnandia Ladina (Cahaya Ilmu Bangsa Institute, 2024)
The Independent Entrepreneurship Program (WMK) is one of the government's initiatives to encourage the development of entrepreneurial potential among students. This time discussing the impact of WMK on the growth of the Robi Toast business developed at the University of 17 August 1945 (UNTAG) Surabaya. Robi Toast, which carries the concept of healthy food made from purple sweet potatoes and mozzarella cheese, is designed to meet market needs for practical, healthy, and nutritious snacks. This study uses a descriptive approach to analyze the effect of this program on various aspects of the business, such as marketing strategy, financial management, increasing sales, and forming a partner network. The results of the study show that WMK has made a significant contribution to the growth of Robi Toast, both in increasing brand awareness and expanding the market.This study uses a descriptive method with a qualitative and quantitative approach. Data were collected through observation, interviews, consumer surveys, and financial analysis. The results of the study show that WMK has made a significant contribution to various aspects of business development, including increasing brand awareness, product diversification, better financial management, and expanding the marketing network.